Combination of Aeration-Adsorption Using Diffuser Aerator and Palmyra Palm Shell Activated Carbon For Groundwater Quality Improvement - Utami, Anggit Salis Media; Mohamad Mirwan; Rizka Novembrianto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study examines the use of a combined aeration-adsorption process utilizing activated carbon derived from Borassus flabellifer (palmyra palm shell) to improve groundwater quality. The aeration process increases dissolved oxygen (DO) levels, facilitating the oxidation of metal contaminants such as iron (Fe) and manganese (Mn). Meanwhile, the activated carbon is used to adsorb any remaining contaminants that are not fully oxidized. The results show that with a 60-minute aeration time, the DO concentration increased to 6.6 mg/L, and Fe and Mn concentrations were reduced by 53.6% and 7.7%, respectively. In the adsorption phase, optimal conditions were achieved at a flow rate of 10 L/h and an adsorption media height of 45 cm, resulting in Fe removal of 63.19%, Mn removal of 99.25%, TDS reduction of 15.51%, and TOC reduction of 17.61%. These findings support the use of the combined aeration-adsorption process as a more environmentally friendly and efficient method for groundwater treatment.